Modified citrus pectin ameliorates methotrexate-induced hepatic and pulmonary toxicity: role of Nrf2, galectin-3/TLR-4/NF-κB/TNF-α and TGF-β signaling pathways - Randa Ismail; Heba A. Habib; Aliaa F. Anter; Amr Amin; Gehan H. Heeba (Frontiers in Pharmacology)
IntroductionMethotrexate (MTX) is a frequently utilized anti-inflammatory and anticancer agent. Its potential liver and lung toxicity often limits its clinical effectiveness. We conducted this study to demonstrate the possible protective impacts of a natural galectin-3 (Gal-3) inhibitor, modified citrus pectin (MCP), against MTX-induced liver and lung toxicity and verify the potential signaling pathways of these suggested effects. In vitro, the cytotoxicity of MCP and its modulatory effect on MTX cytotoxic efficacy were assessed.MethodsFour groups of rats were used: control, MTX (40 mg/kg, single intraperitoneal injection on day 9), MTX + MCP (200 mg/kg/day, orally, for 2 weeks), and MCP alone. MCF7, Nalm6, and JEG3 cell lines were used for the in vitro cytotoxicity assay.ResultsMCP counteracted liver and lung toxicity evidenced by ameliorating the markers of liver and lung functions. Moreover, MCP minimized oxidative stress elicited by MTX in lung and liver tissues, as indicated by reduced malondialdehyde levels, elevated levels of reduced glutathione, increased superoxide dismutase activity, and upregulated Nrf2 protein expression. In hepatic and pulmonary tissues, MCP downregulated the inflammatory signaling pathway, Gal-3/TLR-4/NF-κB/TNF-α. MCP pretreatment decreased TGF-β, collagen content, and cleaved caspase-3 levels. MCP enhanced the cytotoxicity of MTX in Nalm6 and JEG3 and did not interfere with its cytotoxicity in the MCF7 cell lines.DiscussionMCP attenuated MTX-induced liver and lung toxicity through antioxidant, anti-fibrotic, anti-inflammatory, and anti-apoptotic influences, as demonstrated by the improved histopathological changes induced by MTX in pulmonary and hepatic tissues. Moreover, it increased MTX cytotoxicity in different human cell lines.